Aripiprazole for Tourette's syndrome: a systematic review and meta‐analysis. (26th August 2015) - Zheng, Wei; Li, Xian‐Bin; Xiang, Ying‐Qiang; Zhong, Bao‐Liang; Chiu, Helen F. K.; Ungvari, Gabor S.; Ng, Chee H.; Lok, Grace K. I.; Xiang, Yu‐Tao
Abstract : Objective: To review the efficacy and safety of aripiprazole (ARI) for Tourette's syndrome (TS). Methods: This review included randomized controlled trials (RCTs) of children and adolescents (6–18 years) with TS comparing ARI monotherapy with another monotherapies in relation to clinical improvement and adverse events. Results: Six RCTs with a total of 528 subjects (ARI treatment group: n = 253; control group: n = 275) met the inclusion criteria. These included two RCTs (n = 255) that compared ARI monotherapy with tiapride (TIA). Tic symptoms control assessed by Yale Global Tic Severity Scale (Standard Mean Difference (SMD) = −0.38 (Confidence Interval (CI) = −1.32 to 0.56); I 2 = 90%, P = 0.42) revealed no significant differences between the two groups. Extrapyramidal symptoms were significantly different when ARI (1.5%) was compared with haloperidol (HAL) (43.5%). No significant group differences were found in the rates of nausea/vomiting, dizziness, and dry mouth between ARI and TIA (RR = 0.57 to 1.00 (95%CI = 0.14–4.20); I 2 = 0% to 69%, P = 0.35 to 1.00). Conclusion: This review found that ARI has similar efficacy to TIA and HAL for TS, while extrapyramidal symptoms were significantly less with ARI than with HAL. ARI can be considered as an alternative treatment option for TS. Copyright © 2015 John Wiley & Sons, Ltd.